Pengenalan Metode Pembelajaran Kimia Menyenangkan melalui Kit Detektif Kimia bagi Siswa SMA Negeri 1 Kota Bangun: Introduction to a Fun Chemistry Learning Method through Chemistry Detective Kits for Students at SMA Negeri 1, Kota Bangun - Raden Roro Dirgarini Julia Nurlianti Subagyono; Ritbey Ruga; Alda Rizki Aulia; Aditya Sriwahyuningsih; Darin Annissa Shafa Kamila; Wa Sinarti; Olla Mercy Grace Silitonga; Arni Anugrah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Chemistry is one of the elective subjects at the secondary education level that some students find difficult because it involves abstract concepts and is full of symbols. This condition necessitates learning innovation that offers a fun chemistry learning experience for students. This community service activity, conducted by the Chemistry Department, Faculty of Mathematics and Natural Sciences, Mulawarman University, aimed to introduce 11th-grade students at SMA Negeri 1 Kota Bangun to a fun chemistry learning method using the Chemistry Detective Kit. This kit was developed as a learning media innovation using a case-solving approach, where students were invited to analyze cases through a series of simple chemistry experiments, mimicking the work of a detective. The activity included group practical work, followed by a discussion of the chemistry concepts underlying each experiment. The results of the activity's evaluation through questionnaires and interviews indicated that participants responded very positively to the activity, both in terms of the materials and the activity's execution, and in its improvement in students' understanding of chemistry. The majority of students felt that each chemistry detective case provided a fun learning experience (71.9% Strongly Agree, 25.0% Agree). The evaluation results also showed that the learning activities in the form of investigative games helped students understand chemistry concepts and motivated them to learn more about chemistry.